ԴԻՍԿՈՒՐՍԸ ՈՐՊԵՍ ՀԱՂՈՐԴԱԿՑՄԱՆ ՍՈՑԻԱԼԱԿԱՆ ՀԱՄԱՏԵՔՍՏ. ՄԻՇԵԼ ՖՈՒԿՈ - Սահակյան Հայարփի (Բանբեր Երևանի համալսարանի. Փիլիսոփայություն, Հոգեբանություն, 2015)
Post-modernist paradigm is associated with the perception of the world as chaos, managed by probabilistic laws or a game of chance and senseless violence of the rampant, hence declared rejection of determinism and the search for truth that leads to undermining credibility metanarratives fragmentation and contradictory discourse. Nonlinearity sense of postmodern discourse contributes to its dialogization and, as a consequence – the interactivity of communication participants. In postmodernism opportunities of local discourses have been expanding, that is not the sign of a number of linear one-dimensional and spatial multilinearity meaning. It is manifested in the form of non-linearity of meaning, leading to the perception of interactivity, i. e. the involvement of the reader in the event that the joint creative activities for the production of the text. This discourse is perceived as a “contact unity”, “game of the rules” and “concepts manipulate the way”, which is due to social norms and values. Foucault’s “Discourse order” was devoted to the analysis of socio-cultural definition, control mechanisms of discourse. Foucault makes a comparative analysis of the performance of discoursive practices with modern culture, both in the context of modern and classical European traditions, which allows him to expose the status of cultural discourse characteristics, determination of integrated socio-cultural patterns shape the discoursive environment, in other words, discourse analysis, which may include representative different levels, exposes discourse the communicative-pragmatic framework that is given to the socio-cultural environment in which the language level is designed, determines discourse as, so-called, “verbal packaging”.